Replacement name for the cicada genus Torresia Sanborn and Heath, 2014 (Hemiptera: Cicadidae: Tibicininae: Tettigadini) and two new combinations - Sanborn, Allen F.; Heath, Maxine S. (Zootaxa, 2017)
Torrescada nom. nov. pro Torresia Sanborn and Heath, 2014 nec Torresia Castelnau, 1875 (Perciformes) and Torresia Brongersma, 1934 (Squamata) is proposed. The species of Torresia Sanborn and Heath are transferred to Torrescada nom. nov. to become Torrescada lariojaensis (Sanborn and Heath, 2014) n. comb., and Torrescada lariojaensis (Sanborn and Heath, 2014) n. comb.